Estado nutricional, estratégias para perda de massa corporal e efeito da redução de carboidratos sobre marcadores sanguíneos e desempenho em atletas de brazilian jiu-jitsu - Matos, Renata Costa (2017)
INTRODUCTION: Brazilian jiu-jitsu is a sport in with weight categories. Because of this, they end up using harmful strategies to fit the categories before the competitions. One of the strategies used is reduction of energy intake, including carbohydrate restriction. However, due to the importance of carbohydrate ingestion for performance, little evidence is available to support effectiveness of carbohydrate restriction for combat athletes. OBJECTIVES: To evaluate the nutritional status and strategies adopted by Brazilian jiu-jitsu athletes; to analyze the effect of two hypocaloric dietary strategies with different proportions of carbohydrate in weight loss and in biochemical markers; to evaluate the effect of carbohydrate reduction on performance and blood markers of energy metabolism and muscle injury. METHODOLOGY: Data will be presented in the format of three articles. Study 1 refers to the nutritional profile and weight loss strategies most adopted by battling athletes. For that, a weight loss questionnaire was applied and the nutritional status, body composition, and hormonal and lipid markers were evaluated. Article 2 is a randomized clinical trial with a monitored dietary intervention of 4 weeks. The sample was distributed in two groups (R-CHO- moderate reduction of carbohydrate and A-CHO- adequate carbohydrate). Before and after the intervention were measured body weight, skinfolds, the concentrations of hematological, immunological markers and serum cholesterol and fractions were measured. Article 3 is a randomized clinical trial, in which athletes were submitted to two protocols of nutritional intervention with duration of 4 weeks: one with moderate reduction of carbohydrates (R-CHO) and another with adequate carbohydrate levels (A-CHO) . Before and after the dietary intervention, the athletes underwent four physical tests to evaluate the performance and before and after the tests, a blood collection was performed to evaluate the markers of energy metabolism and cell injury. RESULTS: A total of 35 athletes participated in study 1, of which 21 (60%) had already used strategies for weight loss. The athletes with higher body mass and higher percentage of fat had higher levels of VLDL and triglycerides, and lower levels of testosterone. In study 2, 18 athletes completed the intervention. Both R-CHO (n = 10) and A-CHO (n = 8) presented weight reduction, BMI and fat percentage, without altering the integrity of hematological and immunological markers. As for cardiometabolic data, the A-CHO group presented elevation in VLDL and triglyceride levels. Regarding study 3, both strategies promoted weight loss without altering athletes' performance. The glycemia increased in both groups only at the pre-intervention time. As for the other markers of energy metabolism, the R-CHO (n=10) group had higher values of lactate and creatinine post-physical test compared to A-CHO (n=6). CONCLUSION: There is a high prevalence of individuals using strategies for rapid weight loss. With this, it is necessary to propose the adoption of efficient and safe methods for gradual weight loss. In this sense, carbohydrate reduction proved to be an efficient and safe strategy, since it promoted weight loss without affecting performance and without altering the integrity of hematological, immunological and cardiometabolic markers.